Nucleotide sequences of the fecBCDE genes and locations of the proteins suggest a periplasmic-binding-protein-dependent transport mechanism for iron(III) dicitrate in Escherichia coli. - Staudenmaier, H (1989)
The fec region of the Escherichia coli chromosome determines a citrate-dependent iron(III) transport system. The nucleotide sequence of fec revealed five genes, fecABCDE, which are transcribed from fecA to fecE. The fecA gene encodes a previously described outer membrane receptor protein. The fecB gene product is formed as a precursor protein with a signal peptide of 21 amino acids; the mature form, with a molecular weight of 30,815, was previously found in the periplasm. The fecB genes of E. coli B and E. coli K-12 differed in 3 nucleotides, of which 2 gave rise to conservative amino acid exchanges. The fecC and fecD genes were found to encode very hydrophobic polypeptides with molecular weights of 35,367 and 34,148, respectively, both of which are localized in the cytoplasmic membrane. The fecE product was a rather hydrophilic but cytoplasmic membrane-bound protein of Mr 28,189 and contained regions of extensive homology to ATP-binding proteins. The number, structural characteristics, and locations of the FecBCDE proteins were typical for a periplasmic-binding-protein-dependent transport system. It is proposed that after FecA- and TonB-dependent transport of iron(III) dicitrate across the outer membrane, uptake through the cytoplasmic membrane follows the binding-protein-dependent transport mechanism. FecC and FecD exhibited homologies to each other, to the N- and C-terminal halves of FhuB of the iron(III) hydroxamate transport system, and to BtuC of the vitamin B12 transport system. FecB showed some homology to FhuD, suggesting that the latter may function in the same manner as a binding protein in iron(III) hydroxamate transport. The close homology between the proteins of the two iron transport systems and of the vitamin B12 transport system indicates a common evolution for all three systems.